Fairness in Europe: A Multidimensional Comparison - Paul Hufe; Andreas Peichl; Paul Schüle; Jelena Todorović (CESifo Forum, 2022)
What is the status quo of fairness in Europe? To answer this question, we have calculated multidimensional equality of opportunity in income, education, and health for 29 European countries in 2019. Our results show that inequalities of opportunity in education and health are lower than in income. Furthermore, inequality of opportunity measures for these outcome dimensions are imperfectly correlated. This pattern has important implications for fairness comparisons across European countries. While the Scandinavian countries still emerge as the places with the most leveled playing field, the opportunity gap between Northern Europe and Southern Europe is much reduced when jointly considering income, education, and health.
Keywords: 330